Abutilon indicum: Bioactive Compounds and Diverse Therapeutic Applications - Srivastava, Shobhit Prakash; Dikshit, Swati; Moharana, Ankita; Chaturvedi, Neha; Sharma, Saurabh; Verma, Preeti (Current Nutraceuticals, 2024)
A large variety of secondary metabolites are found in medicinal plants, and the majority are significant in medicine. One of the well-known plant species used to cure a wide range of human illnesses is Abutilon indicum. The plant Abutilon indicum has a wide range of therapeutic uses, and its varied parts have been employed to cure a wide range of ailments. Numerous bioactive substances, such as polyphenols, flavonoids, alkaloids, saponins, tannins, and glycosides are present in the plant. Potent antioxidant, anti-inflammatory, antibacterial, hepatoprotective, hypoglycaemic, analgesic, sedative, and diuretic activities have been demonstrated in these compounds. Additionally, the plant has been shown to have cytoprotective properties and to guard against DNA damage brought on by oxidative stress. Future research is required to pinpoint the specific bioactive chemicals responsible for the pharmacological effects of Abutilon indicum and the molecular mechanisms underlying the plant's therapeutic uses. Overall, Abutilon indicum has demonstrated great therapeutic potential and deserves further study as a possible source of homeopathic treatments for various illnesses. The present study covers a summary of the phytochemical and ethnomedicinal applications of Abutilon Indicum that would further help in exploring the research in natural medicine.
Keywords: Abutilon Indicum